Dorsal lateral geniculate substructure in the Long-Evans rat: A cholera toxin B-subunit study - Claire B. Discenza; Pamela eReinagel (Frontiers Media S.A., 2012)
The pigmented rat is an increasingly important model in visual neuroscience research, yet the lamination of retinal projections in the dLGN has not been examined in sufficient detail. From previous studies it was known that most of the rat dLGN receives monocular input from the contralateral eye, with a small island receiving predominantly ipsilateral projections. Here we revisit the question using cholera toxin B subunit (CTB), a tracer that efficiently fills retinal terminals after intra-ocular injection. We imaged retinal termini throughout the dLGN at 0.5 um resolution and traced areas of ipsilateral and contralateral terminals to obtain a high resolution 3D reconstruction of the projection pattern. Retinal termini in the dLGN are well segregated by eye of origin, as expected. We find, however, that the ipsilateral projections form multiple discrete projection zones in three dimensions, not the single island previously described. It remains to be determined whether these subdomains represent distinct functional sublaminae, as is the case in other mammals.